Achievements and challenges of the Sakigake designation system in Japan. Issue 10 (22nd March 2021) - Tanaka, Mototsugu; Idei, Mayumi; Sakaguchi, Hiroshi; Kato, Ryosuke; Sato, Daisuke; Sawanobori, Kenji; Kawarasaki, Shuichi; Hata, Toshiyuki; Yoshizaki, Asako; Nakamura, Miki; Ikuma, Mutsuhiro
Abstract : The Sakigake designation system (Sakigake) has been launched to encourage the pioneered development of innovative new medical products for the effective treatment of severe illness in Japan, which allows leveraging the several advantages in prioritized consultation, rapid review, premium drug pricing and extended data‐protection period. We retrospectively analysed the Sakigake products including drugs and regenerative medical products to clarify the achievements and the future issues in this system. From April 2015 to August 2020 (the first 5‐year trial period of Sakigake), 37 products were designated, and 10 of those were approved in Japan in which 7 new active substances achieved the first‐in‐world approvals. Oncology, neurology and cardiovascular disease were the major therapeutic areas, and those 3 accounted for 75.7% of all products. Sakigake achieved some first‐in‐world approvals by the Pharmaceuticals and Medical Devices Agency/the Ministry of Health, Labor and Welfare of innovative new medical products, although in some therapeutic areas, there remains room in stimulating drug development. Abstract :